(untitled) (International Journal of Biology and Chemistry, 2026)
The article comprehensively studies the possibility of obtaining microcrystalline cellulose (MCC) from the husk of sorghum (SbH) (Sorghum Bicolor), an agricultural crop growing in the country. The research comprehensively studied the effective parameters for the production of MCC from SbH, its yield and quality characteristics, as well as physicochemical properties. When using a hydromodule for the extraction of MCC from SbH at a SbH/peroxyacetic acid ratio of 1:16 g/ml, the yield of MCC was high and reached 57.24%. The amount of α-cellulose in the obtained MCC was 61.32%. It has been established that the yield of MCC obtained by this organosolvent oxidation method is 10-25% higher than with the traditional method of alkaline treatment. The obtained MCC can be used as an ingredient in paper and cardboard production, pharmaceuticals, and composite materials. Keywords: Agricultural waste, sorghumbicolor husks, microcrystalline cellulose, organosolvent oxidation, FTIR, crystal structure.